PRINSIP-PRINSIP PRAGMATIK DALAM MATERI PERCAKAPAN BAHASA JEPANG PADA BUKU SHIN NIHONGO CHUKYUU - Rahayu, Poppy; Philiyanti, Frida; Setiawati , Nia (Universitas Negeri Jakarta, 2011)
To be able to master the language within the context of communication, the teaching of foreign languages requires knowledge of the language target. Pragmatic culture as a branch of linguistics which studies the external structure of language, learned to cope with problems of meaning that was one factor difficulty in interacting. Politeness aspects must also be a concern for civility associate the language with the social world, as social reality. Relations with the pragmatics of politeness is that one of the relevant influence of pragmatic theory of language civility is important aspect in learning a second language or foreign language.